Summary of the round table discussion - Latin America - West Africa on hosting open journals - (:unkn) unknown (My University, 2023)
The aim of this round table is to discuss the various facets that are essential to encourage the emergence and sustainability of open access scientific journals in specific contexts, those of the South, namely Latin America and French-speaking Africa.
Keywords: African Research